Evaluating the impact of marketing interventions on sugar-free and sugar-sweetened soft drink sales and sugar purchases in a fast-food restaurant setting - Aila Khan; Anna Uro Evangelista; Maria Estela Varua (BMC, 2023)
Abstract Background Beverages high in added sugar, such as sugar-sweetened soft drinks, continue to be associated with various health issues. This study examines the effects of a manufacturer-initiated multicomponent intervention on the sales of sugar-free (SFD) and sugar-sweetened (SSD) soft drinks and the amount of sugar people purchase from soft drinks in a fast-food restaurant setting. Methods A database of monthly sales data of soft drinks from January 2016 to December 2018 was obtained from three treatment and three control fast-food restaurants. A multicomponent intervention consisting of free coupons, point-of-purchase displays, a menu board, and two sugar-free replacements for sugar-sweetened soft drinks was introduced in August 2018 for five months in Western Sydney, Australia. A retrospective interrupted time series analysis was used to model the data and examine the effects of the interventions on SFD and SSD sales and their consequential impact on sugar purchases from soft drinks. The analyses were carried out for volume sales in litres and sugar in grams per millilitre of soft drinks sales. A comparison of these measures within the treatment site (pre- and post-intervention) and between sites (treatment and control) was conducted. Results The interventions had a statistically significant impact on SFDs but not SSDs. On average, SFD sales in the treatment site were 56.75% higher than in the control site. Although SSD sales were lower in the treatment site, the difference with the control site was not statistically significant. The net reduction of 6.34% in the amount of sugar purchased from soft drinks between sites during the experimental period was attributed to the interventions. Conclusions The interventions significantly increased SFD sales and reduced sugar purchases in the short run. Aside from free coupons, the findings support the recommendation for fast food restaurants to nudge customers towards choosing SFDs through point-of-purchase displays and the replacement of popular SSDs with their SFD counterparts.